PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI, KESEJAHTERAAN, DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMP NEGERI 2 KRADENAN KABUPATEN GROBOGAN - Purwati, Eny -; Triyaningsih, SL - (Universitas Slamet Riyadi, 2011)
Â ABSTRACT Leadership styles, communication, welfare and motivation of an element management. Through leadership styles, communication, welfare and increasing employee motivation will affect the performance of teachers in SMP Negeri 2 Kradenan Grobogan. The results showed that leadership style variables significantly influence the performance of teachers; communication variables significantly influence the performance of teachers; welfare variables had no significant effect on teacher performance; variables of work motivation has no significant effect on teacher performance SMP Negeri 2 Kradenan Grobogan. F test results showed a significant effect of leadership style variables, communication, welfare and motivation to work simultaneously or jointly model accuracy on teacher performance SMP Negeri 2 Kradenan Grobogan. The test results showed that the coefficient of determination of the contribution of the effect variable of leadership styles, communication, welfare and motivation to work on teacher performance SMP Negeri 2 Kradenan by 30% and the remaining 70% are influenced by variables that are not investigated by researchers Keywords: leadership styles, communication, welfare, working motivation and performance